2008
DOI: 10.1111/j.1365-2141.2008.07100.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundant anti‐apoptotic BCL‐2 is a molecular target in leukaemias with t(4;11) translocation

Abstract: Summary Chemotherapy resistance from imbalanced apoptosis regulation may contribute to poor outcome in leukaemias with t(4;11). Anti‐apoptotic BCL‐2 expression and target modulation were characterized in cell lines with t(4;11) and BCL‐2 expression was examined in MLL and non‐MLL infant/paediatric leukaemia cases by Western blot analysis and/or real‐time polymerase chain reaction. Cytotoxicity of Genasense™ (Oblimersen Sodium, G3139) alone or combined with cytotoxic drugs was assessed by MTT [(3‐4,5‐dimethylth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…Molecular-cytogenetic classification by MLL status and partner genes was described. 5,16 An apheresis sample from a 6.5-year-old boy (WBC, 408 3 10 3 /mL) with MLL-AF4 ALL was obtained from the Children's Hospital of Philadelphia. Mononuclear cells were enriched by Ficoll-Paque (Amersham, Pittsburgh, PA) centrifugation before cryopreservation of diagnostic specimens.…”
Section: Patient Samples and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular-cytogenetic classification by MLL status and partner genes was described. 5,16 An apheresis sample from a 6.5-year-old boy (WBC, 408 3 10 3 /mL) with MLL-AF4 ALL was obtained from the Children's Hospital of Philadelphia. Mononuclear cells were enriched by Ficoll-Paque (Amersham, Pittsburgh, PA) centrifugation before cryopreservation of diagnostic specimens.…”
Section: Patient Samples and Cell Linesmentioning
confidence: 99%
“…5 Propidium iodide (PI) uptake, activated caspase 3, and terminal deoxynucleotidyltransferasemediated dUTP nick end labeling (TUNEL) assay data were analyzed using CellQuest Pro version 5.2 (BD Biosciences). Cell cycle was modeled in live cells, using ModFit LT (Verity Software House, Topsham, ME).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…They have shown that Bcl-2 elimination yielded rapid loss of leukemic cells and significantly prolonged mouse survival, formally validating Bcl-2 as a rational target for a targeted cancer therapy (Letai et al, 2004). Furthermore, high Bcl-2 levels are observed also in ALL characterized by t(4;11) (Robinson et al, 2008). It has been demonstrated that the equilibrium in the formation of Bcl-2:Bax heterodimers (suppressors of death) and Bax:Bax homodimers (activators of death) appears to be central in the molecular regulation of apoptosis (Coustan-Smith et al, 1996).…”
Section: Apoptosis Modulatorsmentioning
confidence: 97%
“…The one exception identified, where targeting BCL-2 alone appeared to be sufficient, was MLLr-ALL. Previous studies have demonstrated high expression of BCL-2 in MLLr pediatric ALL 8 and shown activity of the 1st generation BCL-2 antagonists in MLLr-ALL, supporting the findings by Khaw et al 8 It has been recently shown that MLL/ AF4 specifically upregulates the BCL-2 gene but not other BCL-2 family members via DOT1L-mediated H3K79 methylation at the BCL-2 locus, and this may explain the higher sensitivity of MLLr-ALL xenografts to venetoclax. 9 These data suggest that venetoclax alone may be the agent of choice in children with MLLr-ALL, whereas navitoclax may be more efficacious in non-MLL pediatric ALL (see figure).…”
mentioning
confidence: 99%